The Least Developed Countries Report 2012 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2012)
This Report reviews the LDCs' recent economic performance and examines how to enhance developmental impact of remittances and tap into the knowledge pool of its citizens abroad. Given the increasing magnitude of remittances in LDCs, the Report explores both the beneficial as well as possible adverse impacts of this type of private external flow. While remittances are the most visible effect of migration, there are other forms of Diaspora engagement within the home country such as Diaspora knowledge networks that can facilitate technological catch-up in LDCs and therefore enhance development of productive capacities. Through innovative forms of network-based industrial policy, LDCs could offset some of the adverse impacts of brain drain on their economies. The Report concludes with a policy review section containing lessons from international experiences in this area of interest to LDCs.